Managing the Preparation of the 21st Century Competence Accredited Teachers - Kabir, Md. Rasel (2022)
The information technology revolution, which resulted in a paradigm shift, ushered in the twenty-first century, with technological advancements directing employers' attention to abilities such as creativity, critical thinking, problem-solving, communication, and collaboration, which quickly transformed education systems around the world, including Bangladesh. This development necessitated a greater focus on curriculum, textbooks, platforms and resources, which began to reflect content that would empower learners with 21st-century skills, but not on teachers who are from the twentieth century. Hence, some questions arise, which are the research questions of this study as well as to how can teachers with 20th century competencies teach 21st century students to acquire 21st-century skills? Shouldn't they be familiarized, acculturated, and informed of the appropriate teaching and assessment methods? This study was designed to compile and analyze diachronic and sampling quantitative and qualitative data from three instruments administered across five universities in Bangladesh over a six-month period. The data was then examined utilizing interpretive research findings, which revealed specific reasons favoring the incorporation of the 21st century skills in teacher education. The study's findings backed up the idea that curriculum change, teacher training, and collaboration are the only options for successfully empowering teachers to impart 21st-century skills required for teaching and learning.